The Effects of Technology Use in Later Life on Life Satisfaction, Loneliness, and Well-Being: A Qualitative Study of Multinational Older Adults - Ehmann, Sebastian; McConatha, Jasmin Tahmaseb (Advances in Social Sciences Research Journal, 2023)
Technology use has dramatically increased over the past ten years. While older adults tend to use technology less than younger adults, the "digital divide" is shrinking. Due to technology’s increasing global impact, understanding the differences in use and how it impacts the user is crucial. Studies have identified numerous benefits of technology, particularly during the pandemic; the potential cost of overuse among older adults, possible technology addiction, and cyber dissociation have yet to be fully explored. Although recent research observed a higher risk of young individuals becoming addicted to technology, older adults, particularly older immigrants who may have globally dispersed social networks, are also at risk. Technology use among older adults has been shown to have multiple benefits in combating the worldwide loneliness and isolation epidemic. This exploratory qualitative research investigates how technology and internet use influence a group of multinational older adults’ well-being, life satisfaction, loneliness, and isolation. Fifteen semi-structured interviews were conducted with multinational adults over 60 who are fully or partially retired. Thematic analysis revealed four major themes: Support, Information, Communication, and Balance. Technology access and competence generally provided participants with a vital source of support (personal and professional) and cultural connectivity. Concerns about technological competence were rare, and use amounts were high. Participants used technology to be well-informed about topics of interest, such as politics. They used their devices for reading, watching videos, planning trips, getting health information, or other small practical matters. The most beneficial aspect for most participants was their ability to communicate with friends and family who lived far away. Lastly, participants stressed the need to use technology in a balanced way. However, most participants had no issue separating technology from other fulfilling real-life activities and generally stated that technology played a positive and supportive role in their lives.